Effects of a mindfulness-based leadership training on leadership behaviors and effectiveness - TAN, Nina (Institutional Knowledge at Singapore Management University, 2023)
Objectives: Organizations increasingly integrate mindfulness elements into their leadership development. However, there is limited evidence supporting the efficacy of mindfulness-based leadership training (MBLT) due to a scarcity of intervention studies. Theoretically, little is known about mediating mechanisms through which MBLT might affect leadership effectiveness. Thus, this research examined whether MBLT can improve leadership effectiveness and whether leadership behaviors mediated this effect.MethodsWe conducted a quasi-experimental study conducted in a real-world setting with an active control condition. Sixty leaders from various industries participated in either a 2-day intensive MBLT workshop followed by three individual coaching sessions over 3 months, or a presentation skills training with the same structure. Ninety individuals (subordinates, peers, supervisors) provided ratings of leadership behaviors and effectiveness. Results: Compared to the active control condition, the MBLT led to an increase in leadership effectiveness as well as transformational, authentic, and contingent reward leadership behaviors and a decrease in behaviors that are indicative of avoiding responsibilities and decisions. The former three leadership behaviours mediated the intervention's effect on leadership effectiveness in simple mediation analyses. However, in a multiple mediation analysis, only transformational and authentic leadership were significant mediators, suggesting they were involved in the main mediating mechanisms of the effect. Conclusions: The results provided evidence for the efficacy of an MBLT in enhancing leadership effectiveness through its effects on leadership behaviors. This study contributes to the existing body of knowledge on leadership development, mindful leadership, and mindfulness in the workplace. Preregistrations: This study was not preregistered.